Indian society : continuity change and development - Reddy,P.Sudhakar (Ed.); Gangadhar, V. (Ed.) (New Delhi, 2002)
This book, in honour of Prof. M. Suryanarayana, a distinguished social anthropologist-is a compilation of contributions related to Indian society. The distinguished contributors cover a wide range of issues broadly grouped under three sections: Continuity and change; Women and aging and development. These articles not only provide deeper insights into specific issues but also give new directions for future research. An empirical and secondary data, these analytical works provide a valuable framework to know about the processes of social change in Indian society. This book will be useful for postgraduate students and researches in various social science and behavioural disciplines
Keywords: Societies-India